Therapeutic ultrasound treatment for the prevention of chronic kidney disease-associated muscle wasting in mice - Chen-Yu Lin; Te-I Weng; Jui-Zhi Loh; Ding-Cheng Chan; Chih-Kang Chiang; Kuan-Yu Hung; Shing-Hwa Liu (Artificial Cells, Nanomedicine, and Biotechnology, 2023)
AbstractLow-intensity pulsed ultrasound (LIPUS) is a kind of therapeutic ultrasound. It can help improve bone fracture repair and soft tissue healing. Our previous study found that LIPUS treatment could halt the chronic kidney disease (CKD) progression in mice; unexpectedly, we observed the improvement of CKD-reduced muscle weights by LIPUS treatment. Here, we further tested the protective potential of LIPUS on CKD-associated muscle wasting/sarcopenia using the CKD mouse models. Mouse models of both unilateral renal ischemia/reperfusion injury (IRI) with nephrectomy and adenine administration were used to induce CKD. LIPUS with condition of 3 MHz, 100 mW/cm2, 20 min/day was applied to the kidney of CKD mice. LIPUS treatment significantly reversed the increased serum BUN/creatinine levels in CKD mice. LIPUS effectively prevented the decrease in grip strength, muscle weight (soleus, tibialis anterior, and gastrocnemius muscles), cross-section areas of muscle fibres, and muscular phosphorylated Akt protein expression by immunohistochemistry, and the increase in muscular atrogenes Atrogin1 and MuRF1 protein expression by immunohistochemistry in CKD mice. These results indicated that LIPUS could help improve weak muscle strength, muscle mass loss, muscle atrophy-related protein expression, and Akt inactivation. LIPUS application may be an alternative non-invasive therapeutic intervention on the management of CKD-associated muscle wasting.